2012
DOI: 10.3389/fphys.2012.00228
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exosomes/Microvesicles in the Nervous System and Use in Emerging Therapies

Abstract: Extracellular membrane vesicles (EMVs) are nanometer sized vesicles, including exosomes and microvesicles capable of transferring DNAs, mRNAs, microRNAs, non-coding RNAs, proteins, and lipids among cells without direct cell-to-cell contact, thereby representing a novel form of intercellular communication. Many cells in the nervous system have been shown to release EMVs, implicating their active roles in development, function, and pathologies of this system. While substantial progress has been made in understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
224
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(227 citation statements)
references
References 211 publications
(267 reference statements)
1
224
0
2
Order By: Relevance
“…Exosomes are endosome-derived small membrane vesicles, approximately 30 to 100 nm in diameter, and are released into extracellular fluids by cells in all living systems (12,13). They are present in biofluids such as blood and the cerebrospinal fluid (CSF) (13).…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are endosome-derived small membrane vesicles, approximately 30 to 100 nm in diameter, and are released into extracellular fluids by cells in all living systems (12,13). They are present in biofluids such as blood and the cerebrospinal fluid (CSF) (13).…”
Section: Introductionmentioning
confidence: 99%
“…Originally thought to be a cellular mechanism for disposal, exosomes are now known to have important functions including immune regulation, modulation of inflammation, cell‐to‐cell signaling, and angiogenesis. Exosomes are known to be released from living neurons as part of normal neuronal development as important drivers of synaptic plasticity 21, 22, 23. Increased levels of exosomes and microparticles have been reported to be released from cells after traumatic brain injury24 and stroke,25 which may increase peripheral exosome yields.…”
Section: Discussionmentioning
confidence: 99%
“…Because presynaptic RAB11 knockdown prevents the transfer of Wingless across the NMJ, it was suggested that WLS and Wingless could be loaded together on exosomes that would then traverse the NMJ (Koles et al, 2012). Other studies have also suggested a role for exosomes in neuronal development and function (Lai and Breakefield, 2012), including axon pathfinding (Campbell and Peterson, 1993) and the regulation of myelination (Bakhti et al, 2011).…”
Section: Exosomes In the Context Of Wnt Signallingmentioning
confidence: 99%